ADMINISTRATIVE LAW AND ADMINISTRATIVE PROCEDURE IN THE CONTEXT OF MARTIAL LAW AND EURO-ATLANTIC INTEGRATION OF UKRAINE - Kalyuzhnyi, Rostislav; Shapenko, Lyudmila (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
A review of the textbook "Administrative Law and Administrative Procedure in the Context of Martial Law and Euro-Atlantic Integration of Ukraine". The authors of the review highlight that the publication is notable for its innovation in the field of administrative law and administrative procedure. This textbook is distinctive from other similar publications in both content and structure. It is based on a contemporary conceptualisation of administrative law and procedure, which is human-centred and oriented towards the aspirations of the Euro-Atlantic integration of Ukraine. Consequently, it will be a valuable addition to the educational curriculum of most institutions of higher legal education in Ukraine. Furthermore, the textbook under analysis can serve as a valuable source of knowledge for those engaged in in-depth study of administrative law and administrative procedure, including students and faculty members of law schools, as well as judges, attorneys, and other legal professionals striving to maintain a high level of professional competence.